Persepsi pekerja terhadap keperluan perkhidmatan kaunseling :satu kajian di sektor perindustrian kilang Komag, Sarawak - Norizah, Alias (Universiti Malaysia Sarawak, UNIMAS, 2006)
The objective of this study was to examine the relationships between workers problems and their perception towards the needs of counse l ling services among married and single workers. This study examined the differences of perceptions on the needs of counselling services among workers. The respondents were 263 workers from manufacturing company. Analysis from Pearson Correlation showed no relationship between emotional problem, social problem and work - related problem with the needs for cou nselling services. Using the One - way ANOVA this study indicated that no differences on perception towards the needs of counselling services among races. T - test showed that no differences on perception towards the needs of counse l ling services based on gend er with marital status. Furthermore, the recommendations and limitations were discussed .